Russian Federation : Report on Post-Program Monitoring Discussions. (IMF Staff Country Reports; Country Report ;, 2001)
Economic developments in 2000 have dominated by the strength of the balance of payments. Real GDP has grown by 7.5 percent in 2000, but the momentum has slowed during the year. The external current account surplus is estimated at USD 45 billion (18 percent of GDP) in 2000, driven by the sharp increase in international energy prices and still compressed imports from the pre-crisis period. The budget has recorded a strong surplus in 2000, even though the fiscal stance has relaxed during the fourth quarter.